Son preference and children sex composition in Uttar Pradesh: An empirical analysis - Singh, Jayendra K.; Singh, Gyan P.; Singh, Sanjay K. (The Scientific Temper, 2023)
This study aims to explore the effect of son preference on the sex composition of children in Uttar Pradesh, India’s most populous state, using data from NFHS-IV (2015-16). While national-level estimates have been unable to detect the impact of son preference on the sex composition of children ever born across all families, this research seeks to uncover distinct and predictable patterns at the family level within Uttar Pradesh. The term son preference denotes a prevailing mindset wherein sons are accorded greater significance and value compared to daughters. By examining empirical evidence from Uttar Pradesh, this article highlights two primary effects of son preference on the children sex composition at the family level. Firstly, the data reveals that smaller families are significantly more likely to have sons, while girls tend to be found in larger households on an average. This suggests that families with a higher number of girl children tend to expand their size in an effort to have more sons. Secondly, the study confirms that son preference is associated with various factors, including the age of women, residence background, level of education, family structure, religion, survival status of the last child, and the sex of the last child born. Particularly, the preference for sons is found to be strongest among women, especially elderly women, with lower education levels, belonging to joint families, residing in rural areas of Uttar Pradesh, and being part of lower-caste and Muslim communities, and especially if their last-born child is female. Furthermore, it is established that when family size is controlled then characteristics of women/couples with strong son preference will be same as those women/couples with more sons and if family size is not controlled then the characteristics of women desiring a higher proportion of sons will slightly differ from those women who actually have a higher proportion of sons. These findings shed light on the complex interplay of cultural and socioeconomic factors that influence child sex composition and provide valuable insights for policy interventions aimed at addressing gender imbalances in Uttar Pradesh and beyond